2020
DOI: 10.1186/s13568-020-01114-3
|View full text |Cite
|
Sign up to set email alerts
|

Nigella A ameliorates inflammation and intestinal flora imbalance in DSS induced colitis mice

Abstract: Nigella A, also named Sieboldianoside A, has been extracted from many kinds of Traditional Chinese Medicine (TCM), such as Nigella glandulifera, Stauntonia chinensis DC., and the leaves of Acanthopanax sieboldianus. Nigella A exhibited potential analgesic, anti-inflammatory, anti-tumor, and antioxidant activities. However, whether Nigella A could treat ulcerative colitis (UC) is still unknown. As saponins always be regarded as the kinds of ingredients that could regulate immunity and intestinal flora. This res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We have found a striking difference of Bacteroides in DSS-treated mice ( Fig. 6 b ), which was similar with the observations reported by Okayasu et al and Hu et al 32 , 33 . Moreover, it has been reported that mice transplanted with Bacteroides fragilis could develop persistent colitis 34 .…”
Section: Discussionsupporting
confidence: 92%
“…We have found a striking difference of Bacteroides in DSS-treated mice ( Fig. 6 b ), which was similar with the observations reported by Okayasu et al and Hu et al 32 , 33 . Moreover, it has been reported that mice transplanted with Bacteroides fragilis could develop persistent colitis 34 .…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Figure a, an obvious difference in the microbial diversity was observed among the NC, DSS, and HT-treated groups ( p < 0.05). The Shannon index (community diversity) of the DSS treatment group mice decreased by 20.19% compared with the NC group ( p < 0.05), confirming that DSS induced the decrease in the intestinal flora diversity in mice . The abatement of the gut microbial diversity in HT-L- and HT-H-treated groups was improved by 4.60 and 13.10%, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…The Shannon index (community diversity) of the DSS treatment group mice decreased by 20.19% compared with the NC group (p < 0.05), confirming that DSS induced the decrease in the intestinal flora diversity in mice. 40 The abatement of the gut microbial diversity in HT-L-and HT-H-treated groups was improved by 4.60 and 13.10%, respectively. A similar trend was found in β-diversity, where the DSS-treated group caused significant changes in the diversity of the gut microbiota but the high-dose HT treatment greatly reversed this transformation by shifting it back toward the NC group (Figure 6b).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Intriguingly, we did not see any weight gain in the EV‐stimulated groups, and it is possible that a longer stimulation duration of EV may be required in mice to see recovery in weight. Apart from that, therapeutic investigation of different molecules showed improved histopathology scores without any weight gain indicating weight gain is not always associated with improved disease severity and can be explored further (Hu et al., 2020 ; Xue et al., 2023 ). Colon lengths in the EV groups were longer than the DSS‐only group.…”
Section: Discussionmentioning
confidence: 99%